Philosophy in basic education: concepts and practices secondary school teachers - Wanderley da Silva (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This text derives from a practical activity developed in discipline Philosophy Teaching in 2015 and aims to disseminate and reflect on some data extracted from a qualitative survey with high school philosophy teachers. The research sought to conduct a survey of the main methods, resources and teaching goals used by teachers who teach philosophy in the municipalities of Rio de Janeiro, Seropédica, Nova Iguaçu and Paracambi. Besides the data , the analyzes presented here seeking help in elucidating the current stage of discipline in basic education , as well as to reaffirm the importance , challenges and possibilities of philosophical activity at school.